STRATEGI KOMUNIKASI GURU PENDIDIKAN AGAMA ISLAM BAGI ANAK TUNADAKSA DI SMP LB YPAC MEDAN - Tambunan, Nurhalima (Jurnal Ilmiah Al-Hadi, 2018)
Communication between teacher and student in the implementation of learning is crucial to the acquisition of targeted learning outcomes, this is because the purpose of communication is the effort to deliver messages from the communicator to the communicant so that they have the same meaning. Same here the meaning is the same interpretation of a teacher who teaches in class to students. Children with physical impairment are children who have a damaged or disturbed condition as a result of impaired form or obstacles in the bones, muscles, and joints in their normal functioning. This condition can be caused by illness, accident or can be caused due to innate. Access to education for the physically disabled is no different from a normal child, they both have the right to obtain education such as gaining knowledge, abilities, and skills. Although many individual differences are expressed between one child and another, human rights remain the same as are the rights of extraordinary children the same as normal children. The communication strategy of Islamic religious education teachers is expected to be realized properly so that in the delivery of the material gets a foot back, For this reason, the authors convey the results of research in the form of Communication Strategies of Islamic Education Teachers for Tunadaksa children in LB LB YPAC Medan.